Anti‐aging effect of an oral disintegrating collagen film: a prospective, single‐arm study. (9th June 2021) - Lee, Young In; Lee, Sang Gyu; Kim, Eunbin; Jung, Inhee; Suk, Jangmi; Kim, Jihee; Lee, Ju Hee
Abstract: Background: As the average life expectancy increases, skin aging and wrinkles due to photoaging have gained attention. Collagen is closely involved in the process of skin aging. Among the potential methods of drug delivery to the skin, oral disintegrating films show promise for their ability to bypass the loss of active components that is typical of drug absorption via oral administration. This study was conducted to investigate the effect of an oral disintegrating collagen film on skin aging. Methods: We performed a prospective, single‐arm study in a cohort of 22 women to assess the anti‐aging effect of a novel oral disintegrating film containing collagen applied daily over a 12‐week period. We measured the clinical indicators of skin integrity and performed immunofluorescence and high‐performance liquid chromatography analyses of an ex vivo oral mucosa model to compare the absorption rates of collagen films and conventional oral tablets via the mucosa. Results: We found that the oral disintegrating collagen film reduced skin wrinkle depth and number and significantly increased skin elasticity and density. Conclusions: The novel mode of delivery of collagen via oral disintegrating films has a clinically potential anti‐aging efficacy and is safe and convenient for daily use.